Characteristics of pebble‐ and cobble‐sized clasts along the Curiosity rover traverse from Bradbury Landing to Rocknest. Issue 11 (22nd November 2013) - Yingst, R. A.; Kah, L. C.; Palucis, M.; Williams, R. M. E.; Garvin, J.; Bridges, J. C.; Bridges, N.; Deen, R. G.; Farmer, J.; Gasnault, O.; Goetz, W.; Hamilton, V. E.; et al.
Abstract [1] We have assessed the characteristics of clasts along Curiosity's traverse to shed light on the processes important in the genesis, modification, and transportation of surface materials. Pebble‐ to cobble‐sized clasts at Bradbury Landing, and subsequently along Curiosity's traverse to Yellowknife Bay, reflect a mixing of two end‐member transport mechanisms. The general clast population likely represents material deposited via impact processes, including meteorite fragments, ejecta from distant craters, and impactites consisting of shocked and shock‐melted materials from within Gale Crater, which resulted predominantly in larger, angular clasts. A subset of rounded pebble‐sized clasts has likely been modified by intermittent alluvial or fluvial processes. The morphology of this rounded clast population indicates that water was a more important transporting agent here than at other Mars sites that have been studied in situ. Finally, we identified populations of basalt clasts and porphyritic clasts of undetermined composition by their morphologic and textural characteristics; basalts are confirmed by geochemical data provided by ChemCam.